PENDAMPINGAN TENAGA LABORATORIUM MEDIK DI PUSKESMAS JUANDA TERKAIT SAFETY STANDARD DAN BEST PRACTICE DALAM PROSEDUR PLEBOTOMI - Harianja, Edison (Program Studi Teknologi Laboratorium Medis, ITKES Wiyata Husada Samarinda, 2022)
The medical laboratory is an essential facility for clinicians and the public in assisting in establishing diagnoses and evaluating ongoing treatments. Phlebotomy is closely related to medical laboratory examinations. The purpose of this community service is to obtain blood samples in sufficient volume for the required test, taking into account the prevention of pre-analysis interference, inserting them into the correct tube, paying attention to safety, and with as little discomfort as possible to the patient. In order to obtain blood specimens that meet the laboratory test requirements. This activity was carried out by socializing and explaining the community service plan and carrying out assistance for medical laboratory personnel at the Community Health centres regarding safety standards and best practices in phlebotomy procedures. This activity was held from May 11 to 11 June 2020. Most participants were very enthusiastic about the material provided in this activity and hoped that similar activities could be continued as routine activities at the Juanda Health Center.